1985
DOI: 10.1520/jfs11055j
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Circumstances with Pathological Findings in Asphyxial Deaths by Hanging: A Prospective Study of 61 Cases from Seattle, WA

Abstract: Correlation of the circumstances of death with the pathologic findings in this prospective study of deaths by hanging affords insight pertaining to certain of the pathophysiologic mechanisms involved in fatalities of this type. The presence of conjunctival and facial/periorbital petechial hemorrhages correlates with increasing levels of body support below the point of ligature suspension. Hyoid bone and/or thyroid cartilage fractures (found in 26% of cases) are most frequently identified in those persons found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
3

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 1 publication
10
56
3
Order By: Relevance
“…It can be said in conjunction with the available data that these haemorrhages are the most common finding in the cervical region in cases of fatal hanging. Nonetheless, a number of papers on the subject of death by hanging [3,9,15] as well as on the subject of the causative mechanism of haemorrhages in the cervical muscles [1] ignored this well-established finding [12,16]. Studies concerned with cases of delayed death after hanging [11] also did not take these haemorrhages into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…It can be said in conjunction with the available data that these haemorrhages are the most common finding in the cervical region in cases of fatal hanging. Nonetheless, a number of papers on the subject of death by hanging [3,9,15] as well as on the subject of the causative mechanism of haemorrhages in the cervical muscles [1] ignored this well-established finding [12,16]. Studies concerned with cases of delayed death after hanging [11] also did not take these haemorrhages into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…The men's prisons included three Young Offenders' Institutes (prisoners aged [18][19][20][21], three Category 'A' (maximum security) prisons, 12 Category B prisons (establishments for those who do not require maximum security but for whom escape must be made difficult) and one Category C prison (for prisoners who cannot be housed in open conditions but who are unlikely to try to escape). The male prisons were all located within a hundred miles of the study centre.…”
Section: Participating Prisonsmentioning
confidence: 99%
“…Hanging (including ligature use and self-strangulation) is by far the most common method of completed suicide in prison [8,16], and, because of its high chance of fatality [16][17][18][19][20], any act in which the prisoner was seen using a ligature, or there was physical evidence of having used it, was considered nearlethal. 2.…”
Section: Participant Identificationmentioning
confidence: 99%
“…It has been repetitively demonstrated that the incidence of fractures increases with age [7][8][9][10][11][12][13][14][15][16][17]. The role of gender is less clear: some authors found a male predominance of fractures [9,15,18] whereas other observed a female predominance [7,13] or no significant difference between genders [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…complete hanging with feet off the ground or incomplete hanging with body parts partially supporting the weight of the body) [7,9,13,14,20], the type of ligature [7,9,16], the location of the knot or the highest suspension point [9,10,12,13,19] and the suspension time [13,15]. However, most of these studies evaluated these factors independently of the age of the victims.…”
Section: Introductionmentioning
confidence: 99%